Commercial Use of Aircraft Based on Safety Risk - IMASHEVA, Gulnar M.; DOLZHENKO, Nadezhda A.; ANAYATOVA, Raziyam K.; DORONINA, Yelena V. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).10, 2019)
The relevance of the study is due to the fact that not a single sovereign country agrees to allow uncontrolled commercial activity of foreign airlines on its territory. Hence the need for a clear international legal regulation of the rights to carry out such commercial activities. In this context, the article aims to analyze the main forms and methods of commercial activity. Leading approach to the study of this problem is the descriptive method that has afforded revealing peculiarities of terms of commercial agreements and proposed air fares. The materials of the paper imply the practical significance for the university teachers of the economic and legal specializations.